Ending Aging in Super Glassy Polymer Membranes1. (16th April 2014) - Lau, Cher Hon; Nguyen, Phuc Tien; Hill, Matthew R.; Thornton, Aaron W.; Konstas, Kristina; Doherty, Cara M.; Mulder, Roger J.; Bourgeois, Laure; Liu, Amelia C. Y.; Sprouster, David J.; Sullivan, James P.; Bastow, Timothy J.; et al.
Abstract Aging in super glassy polymers such as poly(trimethylsilylpropyne) (PTMSP), poly(4‐methyl‐2‐pentyne) (PMP), and polymers with intrinsic microporosity (PIM‐1) reduces gas permeabilities and limits their application as gas‐separation membranes. While super glassy polymers are initially very porous, and ultra‐permeable, they quickly pack into a denser phase becoming less porous and permeable. This age‐old problem has been solved by adding an ultraporous additive that maintains the low density, porous, initial stage of super glassy polymers through absorbing a portion of the polymer chains within its pores thereby holding the chains in their open position. This result is the first time that aging in super glassy polymers is inhibited whilst maintaining enhanced CO2 permeability for one year and improving CO2/N2 selectivity. This approach could allow super glassy polymers to be revisited for commercial application in gas separations.